Inversion appendicectomy. - Onuoha, C.E.; Hesse, A.A.; Nicholas, R.J.; Appeadu-Mensah, W. (The Nigerian Postgraduate Medical Journal, 2006)
(i) To emphasise that incidental appendicectomy has indications and, to highlight this indications. (ii) To teach that, even when indicated, this procedure should not convert a clean surgical wound into a clean contaminated or even less optimal wound. (iii) To recommend that if an incidental appendicectomy is to achieve (ii) above, inversion appendicectomy is the better option to choose. (iv) To prove that inversion appendicectomy is fast, easy and achieves a similar result as the more popular excision appendicectomy. PATIENTS AND METHODS: This study was carried out in the paediatric surgical unit of Korle-Bu Teaching Hospital Accra, Ghana - between March 2003 and May 2004. Patient Selection: Fifteen patients qualified for enrollment into this study. These were (i) Those who had clear cut indications for incidental appendicectomy, and had it done as an inversion appendicectomy. (ii) Cases of incidental appendicectomy. METHODS: Eleven of these cases were done for intussusceptions and four for malrotation. Only wounds that qualified as clean surgical wounds were included in this study. There was no age or sex discrimination. RESULTS: Follow up on these patients did not reveal any complications. CONCLUSION: Incidental appemdicectomy has well-defined indications. When indicated in clean wound, inversion appendicectomy is the procedure of choice.